Depression in Workplace : A Study at CIMB Bank Api Api Ctr Branch / Suraya Asek @ Eyan Abd Rashik - Abd Rashik, Suraya Asek @ Eyan (2012)
Purpose - Depression and other mental health disorders have a large impact on the quality of life and productivity of millions of individuals worldwide. For employers, mental health disorders are associated with increased health care costs as well as productivity losses in the form of absenteeism, short-term disability absences and reduced on-thejob productivity-known as presenteeism. The purpose of this paper is to review the correlations between work depression and the factors. Beside that the aim is to analyze the depression symptoms among the employees at Cimb Bank Api Api Ctr Branch. Design/methodology/approach - This review summarizes the literature on the depression factors such as responsibility and workload, supervisor and management treatment, work dissatisfaction, workplace environment, and personal conflict. Beside that the experiencing symptoms amongst the employee also have been discussed. Findings - There are strong correlations between the depression factor and work depressive. Also findings indicate that female staffs were scoring higher level of experiencing depression symptoms compare to male staffs. Thus, there were depressions in workplace at Cimb Bank Api Api Ctr branch.